ANTIBIOTIC UTILISATION FOR HOSPITALISED PAEDIATRIC PATIENTS. Issue 8 (11th July 2014) - Alosaily, Y; Conroy, S; Choonara, I
Abstract : Aim: Antibiotics are among the most commonly prescribed drugs in children.1 A one day survey carried out in 21 European countries found that one third of paediatric inpatients received one or more antibiotics.2 Antibiotics are often inappropriately prescribed for viral infections in children.3 Although antibiotic drug prescribing has been relatively well characterised in primary care, there are limited studies describing inpatient antibiotic use.3 The authors wished to analyse the utilisation of antibiotics and their indications in a paediatric hospital, in order to evaluate if antibiotics are prescribed rationally or not. Methods: A prospective study was carried out in the paediatric medical wards in a hospital in the East Midlands area of the UK. Data was collected from patient's medication charts and medical notes over a five month period (Oct 2012–Feb 2013). Result: Data from prescriptions for 500 children was collected. Of these, 229 children (46%) received a total of 298 antibiotics. More than half of them (59%) were under the age of two years. Of these 229 children, 161 received one antibiotic, 66 received two and two received three. Penicillins and cephalosporins accounted for 86% of antibiotic prescriptions. Respiratory diseases were the most common indication for antibiotic use. Twenty seven patients with bronchiolitis, 19 with wheeze, 18 chest infections, 16 with pneumonia and six with tonsillitis received a total of 105 antibiotics. Conclusion: A high percentage of hospitalised children received antibiotics. Children under the age of two years were more likely to receive antibiotics. Antibiotics are still prescribed for children with bronchiolitis and wheeze and other upper respiratory tract infections, despite the prescription of antibiotics not usually being recommended for these diseases.